Study of Learning Methods According to Ibrahim Utsman Muthari' and Washif Aziz in the Book Al-Tarbiyah Al-'Amaliyyah Wa Usus Ṭuruq Al-Tadris - Yessi Septiliani; Basuki Basuki; Nur Kumilatin; Enny Uswiyati (IQRO: Journal of Islamic Education, 2026)
Learning methods are a key component in creating instructional effectiveness. This study aims to explore the concept of learning methods, as presented by Ibrahim Utsman Muthari and Washif Aziz in the book Tarbiyatul Amaliyah Wa Usus Turuq At Tadris, as a solution to low student participation and educator dominance in the contemporary education system. This study is a library research using content analysis techniques on primary sources and related secondary literature. The results show that learning effectiveness depends on the synergy between classical pedagogical values ​​and adaptive methodological innovation. Four main methodological pillars are identified: discourse, democratic discussions, systematic problem-solving, and collaborative project-based learning. The application of these methods not only increases intellectual absorption but also equips students with social-emotional intelligence and independence. The implications of these findings emphasize that the quality of education must be redefined as a meaningful learning process oriented towards character building and practical skills. The integration of the ideas in this book provides a strategic framework for educators to create an inspiring and student-centred learning environment.